Immigrants' Contribution to Innovativeness: Evidence from a Non-Selective Immigration Country - Katharina Candel-Haug; Alexander Cuntz; Oliver Falck (Center for Economic Studies and ifo Institute (CESifo), 2018)
The economic consequences of migration are hotly debated and a main topic of recent populist movements across Europe. We analyze Polish immigration in the context of the 2004 enlargement of the European Union and find a positive and significant spillover effect of the immigrants on the number of local inventors in German counties in 2001-2010. For causal identification, we exploit a historical episode in the Polish migration history to Germany before the fall of the Iron Curtain and construct a shift-share instrument. Our results differ from findings for high-skilled migration to the United States, which is particularly interesting as Polish immigration to Germany was not based on selection by qualification in our period of analysis.
Keywords: J61; O31; 330; migration; innovation